2004
DOI: 10.1038/sj.ijir.3901138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovariectomy and steroid hormones on vaginal smooth muscle contractility

Abstract: The role of steroid hormones in regulating vaginal smooth muscle contractility was investigated. Rabbits were kept intact or ovariectomized. After 2 weeks, animals were continuously infused with vehicle or supraphysiological levels of testosterone (100 lg/day), or estradiol (200 lg/day), for an additional 2 weeks. The distal vaginal tissue was used to assess contractility in organ baths and changes in tissue structure were assessed by histology. Ovariectomized animals infused with vehicle exhibited significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 32 publications
7
66
1
6
Order By: Relevance
“…The decrease in glycogen production would not maintain the low pH level needed in the vaginal fluA non significant muscular atrophy was confirmed in the vaginal muscularis structure of all ovariectomized and both control rat groups resembled results established by previous study [24]. However, some earlier reports showed significant greater atrophy in the muscularis layers after ovariectomy in rabbits and menopause in women, respectively [21,28]. This disagreement may be attributed to the relatively short term after ovariectomy during the present study (4 weeks), which did not allow significant changes in the muscularis layers to emerge in ovariectomized animals.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The decrease in glycogen production would not maintain the low pH level needed in the vaginal fluA non significant muscular atrophy was confirmed in the vaginal muscularis structure of all ovariectomized and both control rat groups resembled results established by previous study [24]. However, some earlier reports showed significant greater atrophy in the muscularis layers after ovariectomy in rabbits and menopause in women, respectively [21,28]. This disagreement may be attributed to the relatively short term after ovariectomy during the present study (4 weeks), which did not allow significant changes in the muscularis layers to emerge in ovariectomized animals.…”
Section: Discussionsupporting
confidence: 44%
“…Menopause was responsible for inducing a reduction in the number of vaginal epithelial layers, and loss of intermediate cells, represented by an overall reduction in epithelial height [20]. Laboratory studies, showed that ovariectomized rabbits, rats, and nonhuman primates had significant decrease in vaginal epithelial height and smooth muscle tissues [5,6,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Both hormones regulate growth, proliferation and secretion function of reproductive tract epithelial cells. Likewise, the changes in concentration of these hormones during the estrus cycle induce hemodynamic changes in the vascular tissue that result in the increment of permeability of blood vessels and humid weight of the uterus (Kim et al, 2004;Vinci et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Penurunan hormon ini juga diikuti dengan penurunan jumlah messenger ribonucleaic acid (mRNA) reseptor estrogen alpha (ERα) dan androgen (AR) yang menyebabnya kemampuan untuk menangkap hormon steroid menjadi menurun pada tikus. 3 Penurunan jumlah sekresi hormon dan sintesa protein reseptornya menyebabkan terjadi masalah kesehatan yang meliputi gejala vasomotor, somatik, urogenital, psikologis, osteoporosis dan gangguan fungsi seksual. Masalah pada vagina diantaranya vagina menjadi kering, atrofi dan dypareunia, penurunan libido dan gangguan lubrikasi vagina merupakan gejala yang menyebabkan menurunnya kualitas seksual pada masa menopause.…”
Section: Pendahuluanunclassified
“…3 Metilasi promoter-CpG island semakin dipercaya sebagai salah satu perubahan molekular yang dapat diobservasi pada proses penuaan. Metilasi dari region yang kaya akan CpG pada bagian promoter gen merupakan perubahan epigenetik yang menyebabkan inaktivasi transkripsi gen tanpa berhubungan dengan abnormalitas gen.…”
Section: Diskusiunclassified